2012
DOI: 10.1111/j.1473-2165.2011.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and instrumental assessment of the effects of a new product based on hydroxypropyl chitosan and potassium azeloyl diglycinate in the management of rosacea

Abstract: SummaryBackgroundRosacea is a chronic inflammatory skin disease affecting mostly facial skin. Its origin is multifactorial. Important steps in its treatment are avoidance of any triggering factor and control of skin inflammation.AimTo assess the benefit of topical applications of a new product (P-3075).Patients/MethodsA randomized, multicenter, double-blind, placebo-controlled, parallel-group, pilot study was carried out to evaluate the efficacy and tolerability of a cream (P-3075) based on 5% potassium azeloy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 11 publications
(23 reference statements)
0
18
0
6
Order By: Relevance
“…found significantly lower values in facial areas with increased erythema (measured with a skin colour imaging system) compared with areas having normal skin colour, and in severe compared with mild/moderate rosacea . Significant skin hydration increases were seen after successful treatment (moisturizers, topical metronidazole, oral tetracyclines) . In two RCTs where patients with ETR and PPR used creams containing silymarin or glycine/chitosan, the placebo groups using vehicle creams without these ingredients also had significantly higher skin hydration after treatment .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…found significantly lower values in facial areas with increased erythema (measured with a skin colour imaging system) compared with areas having normal skin colour, and in severe compared with mild/moderate rosacea . Significant skin hydration increases were seen after successful treatment (moisturizers, topical metronidazole, oral tetracyclines) . In two RCTs where patients with ETR and PPR used creams containing silymarin or glycine/chitosan, the placebo groups using vehicle creams without these ingredients also had significantly higher skin hydration after treatment .…”
Section: Resultsmentioning
confidence: 97%
“…Significant skin hydration increases were seen after successful treatment (moisturizers, topical metronidazole, oral tetracyclines) . In two RCTs where patients with ETR and PPR used creams containing silymarin or glycine/chitosan, the placebo groups using vehicle creams without these ingredients also had significantly higher skin hydration after treatment . Others noticed no significant changes in skin hydration, while rosacea severity decreased after treatment (various topical agents, photodynamic therapy) …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a pilot, multicenter, randomized, double blind, and placebo-controlled study confirmed the efficacy of this fixed combination in erythema and dryness in patients with subtypes I and II rosacea, using both the Mexameter Õ and Corneometer Õ devices (5).…”
Section: Discussionmentioning
confidence: 90%
“…It is obtained by reacting the chloride of azelaic acid with two molecules of glycine and one molecule of potassium hydroxide (3)(4)(5). Azeloglycine, like azelaic acid, has sebostatic and whitening action (3); furthermore, it possesses, thanks to the presence of glycine, a moisturizing effect (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation